Diagnóstico de leptospirosis genital en hembras bovinas faenadas en el cantón Loja - Carrión Sari, Martha Elizabeth (2024)
Bovine leptospirosis is a zoonotic disease, which is of acute course and worldwide spreading, is produced by various serovars of pathogenic Leptospira, thus affecting the economy of the livestock industry due to abortions, infertility and decreased milk production, causing significant economic losses; therefore, the study of genital leptospirosis is of great importance. Hence, this paper’s objectives were: 1). To detect the presence of Leptospira spp. in the reproductive tract of bovine females; and, 2). To determine the frequency of genital leptospirosis in bovine females slaughtered in the canton of Loja. For this purpose, it was taken samples of uterine lavage and follicular aspirate from 50 slaughtered bovine females between November and December 2022. The detection of the bacterium was performed through the conventional PCR method to detect the presence of the 262 bp hap1 gene from pathogenic Leptospira. Finally, the genetic material of the bacteria was detected from ovarian follicles of 4 cows (8%), while in the uterus samples no positive results were recorded. The results constitute a baseline for future research, which allows a deeper understanding of the pathogenesis of the disease and its repercussions at the reproductive level and the frequency with which it occurs in order to establish an organized control program at the local and regional levels.